THE EFFECT OF MULBERRY TYPES ON THE PRODUCTIVITY OF COCOON OF TWO Bombyx mori L SILKWORM HYBRIDS - Lincah Andadari; Minarningsih Minarningsih; Rosita Dewi (Pusbindiklat - LIPI, 2017)
Mulberry (Morus sp.) is the only food for silkworm of Bombyx mori L and larvae that is fed with highly nutritious mulberry leaves will have more resistant to disease and able to produce the better cocoon. The study was aimed to determine the effect of mulberry SULI 01, ASI, and Morus cathayana as feedingmaterials for cocoon production from PS 01 and C 301 silkworm hybrids. The study was arranged in Block Randomized Design, with a factorial design of three type of mulberry’s leaf and two hybrids of silkworm. Feed setup and maintenance of a silkworm cocoon until harvest time was carried out at Cipeuteuy village, Kabandungan, Sukabumi district. The determined parameters were rendement of rearing, the weight of cocoon, the weight of cocoon shell, and cocoon shell percentage. The result showed that rendement of rearing to all treatment was not significantly affected, in which all treatment showed average percentage above 90%. The treatments combination of ASI mulberry and PS01 silkworm hybrid gave the best result for parameters of rendement rearingaround 96.6%, the weight of cocoon 1.78 g, and the weight of cocoon shell 0.37 g, while cocoon cell percentage is around 21.18%. The result of a combination between SULI 01 and PS 01 is rendement rearing around 95.20%, the weight of cocoon 1.6 g, the weight of cocoon shell 0.34 g, and cocoon shell around 21.47%.